(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In order to study the characterization of the tin substituted Fe2TiO5 based materials the samples are prepared by standard ceramic technique. The single-phase formation of the pseudobrookite is confirmed by XRD technique.It is interesting to note that substitution of Ti 4+ by Sn4+ is responsible to increase the unit cell volume and X-Ray or theoretical density. On the other hand, the use of anatase in the reaction causes the decrease in practical density and the increase in the porosity, Debye particle size and the inhomogeneity.